A Review on In Vitro Evaluation of Chemical and Physical Digestion for Controlling Gastric Digestion of Food - Hiroyuki Kozu; Isao Kobayashi; Sosaku Ichikawa (Foods)
Food digestion in the gastrointestinal is a series of processes consisting of chemical and physical digestion. Recently, developing foods with controlled digestion in the stomach may attract more attention. Hydrogel foods are useful tools for designing foods with controlled digestion because it is relatively easy to design their food characteristics by adjusting the type and content of the additives. This review introduces the latest status of in vitro gastric digestion as a food characterization system. The in vitro evaluation of chemical gastric digestion by gastric acid and digestive enzymes focuses on INFOGEST-standardized gastrointestinal digestion protocols for healthy adults, infants, and older adults. For the in vitro evaluation of physical gastric digestion by peristalsis, the current development of gastrointestinal tract devices that precisely or efficiently simulate the shape of the stomach and gastric peristalsis is described. In addition, we introduce studies that have utilized these devices to investigate the gastric digestion behavior of hydrocolloid foods with different mechanical characteristics.